2016
DOI: 10.1126/science.aaf6807
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic field and turbulence of the cosmic web measured using a brilliant fast radio burst

Abstract: Fast radio bursts (FRBs) are millisecond-duration events thought to originate beyond the Milky Way galaxy. Uncertainty surrounding the burst sources, and their propagation through intervening plasma, has limited their use as cosmological probes. We report on a mildly dispersed (dispersion measure 266.5 ± 0.1 parsecs per cubic centimeter), exceptionally intense (120 ± 30 janskys), linearly polarized, scintillating burst (FRB 150807) that we directly localize to 9 square arc minutes. On the basis of a low Farada… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
255
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(276 citation statements)
references
References 73 publications
(102 reference statements)
17
255
1
1
Order By: Relevance
“…20 The factor of (1+z) −1 is a combination of the photon redshift, time dilation, and the frequency −2 dependence of cold plasma dispersion. Ravi et al (2016) also suggested that the extremely low scattering of FRB 150807 compared to its DM may be linked to its origin from a low-mass (<10 9 M e ) galaxy. However, the strong polarization and scattering properties of FRB 110523 do suggest the presence of turbulent magnetized plasma around the source (Masui et al 2015), suggesting that individual FRB environments may be quite diverse.…”
Section: Relation To Dwarf Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The factor of (1+z) −1 is a combination of the photon redshift, time dilation, and the frequency −2 dependence of cold plasma dispersion. Ravi et al (2016) also suggested that the extremely low scattering of FRB 150807 compared to its DM may be linked to its origin from a low-mass (<10 9 M e ) galaxy. However, the strong polarization and scattering properties of FRB 110523 do suggest the presence of turbulent magnetized plasma around the source (Masui et al 2015), suggesting that individual FRB environments may be quite diverse.…”
Section: Relation To Dwarf Galaxiesmentioning
confidence: 99%
“…To date, 18 FRBs have been reported-most of them detected at the Parkes telescope (Lorimer et al 2007;Keane et al 2012Keane et al , 2016Thornton et al 2013;Burke-Spolaor & Bannister 2014;Petroff et al 2015;Ravi et al 2015Ravi et al , 2016Champion et al 2016) and one each at the Arecibo (Spitler et al 2014) and Green Bank telescopes (Masui et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The burst scintillation suggests weak turbulence in the ionized intergalactic medium. The localization of FRB 150807 can be used to estimate the distance at which it was emitted, if it can associated with a star or a galaxy [24]. We will discuss FRB 150807 in Section 4.…”
Section: Burst Astrophysics Short Summarymentioning
confidence: 99%
“…Their origin is still unknown. At the time of writing, eighteen FRBs have been discovered (Lorimer et al 2007;Keane et al 2012;Thornton et al 2013;Burke-Spolaor & Bannister 2014;Masui et al 2015;Petroff et al 2015;Ravi et al 2015Ravi et al , 2016Champion et al 2016;Keane et al 2016), with only one source (Spitler et al 2014 known to repeat. A catalog of these bursts and their properties is made available by Petroff et al (2016).…”
Section: Introductionmentioning
confidence: 99%